Integrated Design Intent of 3D Parametric Models. (May 2022) - Kyratzi, Sofia; Azariadis, Philip
Abstract: The creation of a flexible and robust 3D model that appropriately conveys its design intent is a hard task that mainly relies on the designer's ability to express, through constraints and parameters, the expected behavior of the model. On this basis, we propose an Integrated Design Intent Architecture that aims to communicate the design intent and at the same time to support the design-with-design-intent modeling process. The proposed architecture builds upon the concepts of "intention regularities" and "meta-constraints" that are respectively used to describe common design intentions and the constraining scheme that reflects them. Meta-constraints establish a design intention during the geometric definition of a model and the corresponding intention regularities communicate the design intent at semantic level. Highlights: A constraint-based framework that captures and communicates design intent in parametric solid modeling environments. An analysis of different constraining schemas and their inferring design intent in CAD models. Definition of meta-constraints for capturing a pre-defined design intent through intention regularities. Examples of applying the proposed IDI Architecture for parametric product-design.